The Impact of Economic Policy on Economic Crime - Madai, Sándor (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
This study presents the parallelism of the characteristics of the economic crimes of the Central and Eastern-European countries participating in the project. That is, it notes aspects of criminal law that clearly show that such countries in the past decade employed (and still employ) similar regulatory principles, owing to reasons such as geographical proximity and others. This study provides an overview of the regulatory directions of the countries after World War II, which, from the Soviet sphere of interest, were common. We then review the main steps in the field of action against economic crimes, which can be perceived as stemming from democratization. Notably, most of the examined countries are European Union members, and more countries want to join. Therefore, among the countries, the integration process indeed reveals a similar legal and political background. Considering the limitations of the study, it was not possible to examine the changes in the regulations of each country in detail. Thus, we only tried to draw attention to the similarities of common processes and characteristics.KEYWORDS: Central and Eastern Europe, Eastern Europe, economic crimes, criminal law, European Union